PENGARUH PAJAK REKLAME DAN PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN SIDOARJO TAHUN 2014-2019 - Annisah Febriana (PUTRA JAWA PUBLISHER, 2024)
The purpose of this study is to determine the impact of the advertisement tax and the roadway lighting tax on Local Own Revenue (PAD). The independent variables used in the study were the advertisement tax and the roadway lighting tax, while the dependent variable was Local Own Revenue (PAD). The data used in this study were secondary data obtained from the tax records of the advertisement tax and the roadway lighting tax in Sidoarjo regency from 2014 to 2019. The study was conducted by the Sidoarjo Regency Regional Revenue Office, Sidoarjo District, Sidoarjo Regency, East Java. The inferential statistical method with Double Regression Analysis, F-test, T-test, and SPSS 26 Version was used for analysis. The results of the study showed that the coefficient of the advertisement tax (b1) was 0.954 and the coefficient of the roadway lighting tax (b2) was 95.4%. This means that both the advertisement tax and the roadway lighting tax have a positive effect on Local Own Revenue (PAD). The double regression analysis revealed that the adjusted R2 value was 9.10, indicating that 9.1% of the dependent variable (Local Own Revenue) was explained by the advertisement tax and the roadway lighting tax, while 90.0% was explained by other variables not mentioned in the study. The